2022
DOI: 10.1186/s12913-022-07912-8
|View full text |Cite
|
Sign up to set email alerts
|

Work stress in nurses returning to tertiary a general hospitals in China after the delivery of their second child: a cross-sectional study

Abstract: Objective To investigate the current situation of work stress in nurses returning to work in Chinese tertiary A general hospitals after giving birth to their second child and to analyze influencing factors. Methods From January to April 2021, 448 nurses returning to work after the birth of their second child, working in 23 general hospitals in China, were investigated and completed the postpartum work stress scale and self-rating depression scale. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Five studies (9.62%) addressed job-related wellbeing and working experience at work re-entry. Nurses returning to work after the birth of their second child show a high level of work stress, with the highest score in their mother's role commitment (Chen et al 2022). Work stress seems higher in women with lower family monthly income, time since returning to work, and age of the first child, and in women with higher duration of maternity leave and higher depressive symptoms (Chen et al 2022).…”
Section: Job-related Wellbeing and Working Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Five studies (9.62%) addressed job-related wellbeing and working experience at work re-entry. Nurses returning to work after the birth of their second child show a high level of work stress, with the highest score in their mother's role commitment (Chen et al 2022). Work stress seems higher in women with lower family monthly income, time since returning to work, and age of the first child, and in women with higher duration of maternity leave and higher depressive symptoms (Chen et al 2022).…”
Section: Job-related Wellbeing and Working Experiencementioning
confidence: 99%
“…Nurses returning to work after the birth of their second child show a high level of work stress, with the highest score in their mother's role commitment (Chen et al 2022). Work stress seems higher in women with lower family monthly income, time since returning to work, and age of the first child, and in women with higher duration of maternity leave and higher depressive symptoms (Chen et al 2022). On the other hand, women who have access to breastfeeding supporting conditions at their workplace report better job satisfaction (Wolde et al 2021).…”
Section: Job-related Wellbeing and Working Experiencementioning
confidence: 99%
“…Consequently, previous research findings have indicated that only 57–69% of nurses who completed the Return to Practice Program were able to successfully re-enter the nursing workforce [ 26 ]. These challenges persist even after returning to work, as reported in subsequent studies [ 27 29 ], exacerbated by the absence of family-friendly working conditions, inadequate on-the-job training opportunities, and insufficient ongoing education and mental support to overcome anxiety and regain confidence [ 30 ]. As a consequence, nurses who have returned to work experience a sense of guilt toward both their colleagues and patients for perceived inadequacies in care provision, as well as feelings of guilt toward their families due to the sacrifices necessitated by their work obligations [ 31 ], all of which contribute to higher attrition rates among returners.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in China found that the work scheduling of a female healthcare worker, namely a nurse, affected work stress for breastfeeding working women, particularly when returning to work after giving birth. 6 Another issue was caused by the distance between the mother and the baby due to the demands of the workplace, requiring mothers to spend extended hours away from home, leaving their babies unattended. 7 Study by Sattari et al also suggested that work-related stress among breastfeeding female doctors was associated with the availability of lactation breaks at work.…”
Section: Introductionmentioning
confidence: 99%